2020
DOI: 10.1016/j.anl.2020.05.020
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic value of detecting sudden smell loss among asymptomatic COVID-19 patients in early stage: The possible early sign of COVID-19

Abstract: The newly emerged coronavirus disease 19 , is threatening the world. Olfactory or gustatory dysfunction is reported as one of the symptoms worldwide. As reported so far, different clinical features have been reported according to outbreak sites and gender; most of the patients, who complained of anosmia or hyposmia, were Europeans. We had a fast review for novel articles about COVID-19 infection and olfactory function.Observations: Rapid reviews for COVID-19 or other viral infection and olfactory and/or gustat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
1
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 40 publications
2
30
1
4
Order By: Relevance
“…Another review by Kang et al (21 studies) had similar observations [70]. They found that the use of intranasal or oral steroids enhanced the recovery of COVID-19related olfactory/gustatory dysfunction [70]. We found 11 studies that specifically evaluated gustatory and olfactory functions in patients with COVID-19 infection [71][72][73][74][75][76][77][78][79][80][81].…”
Section: Olfactory and Gustatory Dysfunctionsupporting
confidence: 59%
See 2 more Smart Citations
“…Another review by Kang et al (21 studies) had similar observations [70]. They found that the use of intranasal or oral steroids enhanced the recovery of COVID-19related olfactory/gustatory dysfunction [70]. We found 11 studies that specifically evaluated gustatory and olfactory functions in patients with COVID-19 infection [71][72][73][74][75][76][77][78][79][80][81].…”
Section: Olfactory and Gustatory Dysfunctionsupporting
confidence: 59%
“…They concluded that SARS-CoV-2 may infect neural and oral tissue and thereby present with olfactory and gustatory symptoms. Another review by Kang et al (21 studies) had similar observations [70]. They found that the use of intranasal or oral steroids enhanced the recovery of COVID-19related olfactory/gustatory dysfunction [70].…”
Section: Olfactory and Gustatory Dysfunctionmentioning
confidence: 83%
See 1 more Smart Citation
“…In Brazil, a study carried out with 253 recovered patients, showed that 212 had experienced sudden-onset anosmia and 196 had developed loss of smell accompanied by nonspecific inflammatory symptoms [ 6 ]. Sudden changes in smell thus came to be seen as initial signs of COVID-19 [ 7 ] and, anosmia, in the absence of other symptoms, such as rhinorrhea or nasal congestion, may be an indicator of SARS-CoV-2 infection [ [8] , [9] , [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…Identifying and isolating asymptomatic patients is critical for preventing the rapid spread of COVID-19. Considering the reports of smell dysfunctions and their predictability [ 21 , 22 ], we hypothesized that a multitude of olfactory dysfunctions could occur in asymptomatic carriers [ 9 , [23] , [24] , [25] , [26] ]. Assessing minor dysfunctions may not be possible with traditionally used methods due to the lack of precision in delivering stimuli to individuals [ 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%